Efficiency and usability of an elementary hand-held suction assembly in paediatric tracheostomised patients. Issue 11 (13th November 2022) - Sagar, P; Kumar, R; Chandran, A
Abstract: Objective: Commercially available suction devices are expensive, large and heavy, and need electricity, and thus restrict the outdoor activity of tracheostomised children and their carers. This study evaluated the efficacy and usability of a simple suction assembly using a syringe and feeding tube in paediatric tracheostomised patients. Methods: Following the domiciliary usage of this suction assembly instead of their existing suction device for a minimum of 15 days, carers responded to a set of questionnaires containing a subjective scoring system. Results: Ninety-three per cent of the carers considered this assembly as average, good or very good in cleaning the tracheostomy tube. Eighty per cent of the carers considered that this assembly would be suitable when their existing suction machines are unavailable, indicating high usability, and 66.67 per cent of the carers would be confident using this assembly in outdoor settings. Conclusion: Larger studies with objective evaluation methods can validate the high efficacy of this simple, inexpensive and easy-to-use, hand-held suction apparatus as reported by the carers of 15 paediatric tracheostomised patients in this study.